Use of endoscopy for management of acute upper gastrointestinal bleeding in the UK: results of a nationwide audit. Issue 8 (31st March 2010) - Hearnshaw, Sarah A; Logan, Richard F A; Lowe, Derek; Travis, Simon P L; Murphy, Mike F; Palmer, Kelvin R
Abstract : Objectives: To examine the use of endoscopy in the UK for acute upper gastrointestinal bleeding (AUGIB) and compare with published standards. To assess the organisation of endoscopy services for AUGIB in the UK. To examine the relationship between outcomes and out of hours (OOH) service provision. Design: Multi-centre cross sectional clinical audit. Setting: All UK hospitals accepting admissions with AUGIB. Patients: All adults (≥16 yrs) presenting with AUGIB between 1st May and 30th June 2007. Data Collection: A custom designed web-based reporting tool was used to collect data on patient characteristics, comorbidity and haemodynamic status at presentation to calculate the Rockall score, use and timing of endoscopy, treatment including endoscopic, rebleeding and in-hospital mortality. A mailed questionnaire was used to collect data on facilities and service organisation. Results: Data on 6750 patients (median age 68 years) were analysed from 208 hospitals. 74% underwent inpatient endoscopy; of these 50% took place within 24 h of presentation, 82% during normal working hours and 3% between midnight and 8 am. Of patients deemed high-risk (pre-endoscopy Rockall score ≥5) only 55% were endoscoped within 24 h and 14% waited ≥72 h for endoscopy. Lesions with a high risk of rebleeding were present in 28% of patients of whom 74% received endoscopic therapy. Further bleeding was evident in 13% and mortality in those endoscoped was 7.4% (95% CI 6.7% to 8.1%). In 52% of hospitals a consultant led out of hours (OOH) endoscopy rota existed; in these hospitals 20% of first endoscopies were performed OOH compared with 13% in those with no OOH rota and endoscopic therapy was more likely to be administered (25% vs 21% in hospitals with no OOH rota). The risk adjusted mortality ratio was higher (1.21, p=0.10, (95%CI 0.96 to 1.51)) in hospitals without such rotas. Conclusions: This audit has found continuing delays in performing endoscopy after AUGIB and underutilisation of standard endoscopic therapy particularly for variceal bleeding. In hospitals with a formal OOH endoscopy rota patients received earlier endoscopy, were more likely to receive endoscopic therapy and may have a lower mortality.